Problematic internet use and health outcomes: does trait self-control matter? - Ibrahim, Najafi Auwal; Kura, Kabiru Maitama; Dasuki, Salihu Ibrahim; Alkali, Abubakar Mohammed (Universiti Utara Malaysia, 2020)
Problematic internet use is prevalent among university students, and it has been associated with increased adverse health outcomes. The results of existing research are mixed regarding the effects of problematic internet use on health outcomes. To resolve this ambiguity, we drew upon the self-control theory and person-situation interaction model to propose trait self-control as a moderator in the relationship between problematic internet use and adverse health outcomes. The study participants comprised 273 students from both public and private universities in Nigeria. Results reveal that problematic internet use is a significant predictor of adverse health outcomes. However, we find no evidence to support our postulated Hypothesis that trait self control moderates the effects of problematic internet use on adverse health outcomes. Implications, limitations, and potential for future research are highlighted.